Analisis Kreativitas Siswa Kelas V dalam Pemanfaatan Barang Bekas di SD Negeri 1 Mayakeli pada Mata Pelajaran SBdP - Wutabisu, Edgar renaldy; Lagandesa, Yun Ratna Lagandesa; Andhika Pratama, Ryan; Hariana, Kadek (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2023)
This study aims to describe the implementation of SBdP (Cultural Arts and Craft) learning in fifth-grade students at SD Negeri 1 Mayakeli. This type of research is qualitative. The subjects of this study were fifth-grade students of SD Negeri 1 Mayakeli for the 2023/2024 academic year, consisting of 15 students—7 female and 8 male students. Data analysis includes observation guidelines, interviews, documentation, and questionnaires. The study results on the analysis of fifth-grade students' creativity in utilizing recycled materials in the SBdP subject at SD Negeri 1 Mayakeli show that students are enthusiastic about participating in the SBdP subject when they are given guidance, motivation, and encouragement at the beginning of the lesson. The teacher encourages active student participation during learning through creative activities, such as students being able to appreciate, recognize, value, and assess an artwork produced from a useful handicraft product that has aesthetic value for both students and others. The ideal characteristics of SBdP include a recreational nature through experimentation, courage in expressing opinions, and are implemented both in an integrated or single subject manner. The methods used during learning are the question-and-answer method and games in learning to prevent students from feeling bored during the teaching and learning process. The teacher also occasionally uses themselves as a learning medium, depending on the material presented, to help students better understand the material being taught.